(untitled) (Research, Society and Development, 2020)
This work is a bibliographic review of works by various authors on scientific writing. The aim of this study was to develop a guiding to the student during the process of preparing a quality master’s dissertation. Almost all stricto sensu postgraduate programs - at the master’s degree - require the writing and delivery of a dissertation in order to completion of the course and obtaining the master’s degree in the specific area. However, the preparation of this report is not an easy task and it requires a set of the researcher’s skills. In this context, many authors have confirmed the low quality of the dissertations, which is a concern worldwide. Thus, this article aims to present a set of guidelines for the elaboration of a good masters dissertation, through bibliographical analysis of the most recent articles about this theme. As a result, we presente a compilation of the main guidelines for dissertation writing, in terms of structure and content. We conclude that it is too important and necessary to consolidate the preparation of masters students for scientific writing.